Aural Textiles: From listening to pattern making. Issue 1 (1st August 2019) - Jaramillo, George; Mennie, Lynne
Textile patterns, whether printed, knitted, woven or embroidered, tend to be inspired by and created in response to the visual environment. The soundscape is a significant component of the embodied multisensory landscape – from the buzz of fluorescent tube lights in an office to the intermittent roar of water flowing in a river; no space is ever silent (Schafer 1994). Attunement to environmental soundscape provides inspiration in music, art and, in this case, the creation of textile patterns, challenging the visual bias of pattern creation. In this ongoing study, the audio sources from bird song to horses galloping are visualized into spectrograms forming contemporary landscape-inspired textile patterns. Spectrograms are a type of visualization of an audio spectrum where the intensity and multiple frequencies are displayed across time, rather than simply the pitch and amplitude of the sound source. These spectrograms are then transformed into textile patterns through the interaction between a maker's existing skill set and digital software. By sharing this process with a group of textile practitioners, this sound-to-visual approach forms the foundation of a co-created textile pattern design. In this way, the process of soundscape-inspired design challenges the visual bias of existing textile patterns, contributing to the sensory ethnography of the contemporary landscape. Here we explore key insights that emerged from the project – experimenting, collaborating and disrupting – through the imagery of process and pattern making, as well as, through the narratives and reflections of the practitioners, presenting a collective visual encounter. In the end, the project opens dialogues to collaboratively understand and relate to the local soundscape as a source of inspiration for pattern making, and begins to formalize a design narrative based on the non-visual environment.